(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The Genre of Autobiography, particularly in Indo-Anglianliterature, has not received its due attention by critics as well as Researchscholars. Despite the best of writerswith their rich harvest of autobiographical output, barring a few criticalworks, no one has seriously attempted to work upon this theme. In this article,I have tried to trace the beginnings of the genre of autobiography in Ancientand Medieval India and later in British India till the end of 19thcentury. However I wish to enlarge my scope of writing and critically examinethe genre of autobiography by making a special study of select autobiographersunder the title “ A Critical Evaluation of Indo-Anglian Autobiography – A selectstudy”